MISKONSEPSI PENERAPAN PEMBELAJARAN BERDIFERENSIASI DI SEKOLAH DASAR - Somantri, Diki; Sutanto, Tono; Yasmin Istiqomah, Yunita (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Differentiated learning is a trend that is promoted at various school levels, one of which is in elementary school, but its implementation is often constrained by misconceptions or failure of a teacher in implementing a method or approach. This study examines the misconceptions faced by teachers in implementing differentiated learning, the factors that cause them, and their impact on learning effectiveness. This research uses qualitative research, data collection techniques in this research include literature study and observation. Analysis of data obtained in the field and literature review shows misconceptions in the form of misunderstanding of basic concepts, lack of adequate training, and lack of infrastructure support. In this study, the researcher suggests concrete steps to overcome misconceptions and improve the implementation of effective differentiated learning.